Differentiating neurosarcoidosis from multiple sclerosis using combined analysis of basic CSF parameters and MRZ reaction - Vlad, Benjamin; Neidhart, Stephan; Hilty, Marc; Ziegler, Mario; Jelcic, Ilijas (Frontiers in Neurology, 2023)
Background Neurosarcodosis is one of the most frequent differential diagnoses of multiple sclerosis (MS) and requires central nervous system (CNS) biopsy to establish definite diagnosis according to the latest consensus diagnostic criteria. We here analyzed diagnostic values of basic cerebrospinal fluid (CSF) parameters to distinguish neurosarcoidosis from MS without CNS biopsy. Methods We retrospectively assessed clinical, radiological and laboratory data of 27 patients with neurosarcoidosis treated at our center and compared following CSF parameters with those of 138 patients with relapsing-remitting MS: CSF white cell count (WCC), CSF/serum albumin quotient (Qalb), intrathecal production of immunoglobulins including oligoclonal bands (OCB), MRZ reaction, defined as a polyspecific intrathecal production of IgG reactive against ≥2 of 3 the viruses measles (M), rubella (R), and zoster (Z) virus, and CSF lactate levels. Additional inflammatory biomarkers in serum and/or CSF such as neopterin, soluble interleukin-2 receptor (sIL-2R) and C-reactive protein (CRP) were assessed. Results There was no significant difference in the frequency of CSF pleocytosis, but a CSF WCC > 30/μl was more frequent in patients with neurosarcoidosis. Compared to MS, patients with neurosarcoidosis showed more frequently an increased Qalb and CSF lactate levels as well as increased serum and CSF levels of sIL-2R, but a lower frequency of intrathecal IgG synthesis and positive MRZ reaction. Positive likelihood ratio (PLR) of single CSF parameters indicating neurosarcoidosis was highest, if (a) CSF WCC was >30/μl (PLR 7.2), (b) Qalb was >10 × 10−3 (PLR 66.4), (c) CSF-specific OCB were absent (PLR 11.5), (d) CSF lactate was elevated (PLR 23.0) or (e) sIL-2R was elevated (PLR>8.0). The combination of (a) one of three following basic CSF parameters, i.e., (a.1.) CSF WCC >30/ul, or (a.2.) QAlb >10 × 10−3, or (a.3.) absence of CSF-specific OCB, and (b) absence of positive MRZ reaction showed the best diagnostic accuracy (sensitivity and specificity each >92%; PLR 12.8 and NLR 0.08). Conclusion Combined evaluation of basic CSF parameters and MRZ reaction is powerful in differentiating neurosarcoidosis from MS, with moderate to severe pleocytosis and QAlb elevation and absence of intrathecal IgG synthesis as useful rule-in parameters and positive MRZ reaction as a rule-out parameter for neurosarcoidosis.